2018
DOI: 10.1590/s1517-707620180004.0555
|View full text |Cite
|
Sign up to set email alerts
|

Obtenção de extratos secos de carotenoides a partir da biomassa da microalga Haematococcus pluvialis por secagem em torre de aspersão (spray-drying)

Abstract: RESUMO Os carotenoides compreendem uma classe de mais de 600 pigmentos naturais, cujo potencial biológico está relacionado à sua atividade antioxidante, regulação do crescimento celular, modulação da resposta imune e da atividade anti-inflamatória. A Haematococcus pluvialis é uma microalga verde, conhecida por sintetizar e acumular grandes quantidades de carotenoides, entre estes a astaxantina. Este trabalho teve como objetivo preparar e caracterizar extratos secos de H. pluvialis pela técnica de secagem em to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The extracts produced with colloidal silicon dioxide had better flow characteristics and a reduced tendency to agglomerate compared to other adjuvants. However, the high load of the plant constituents and reduced particle sizes could cause flow problems, which could lead to unfavorable behavior in conditions of environmental humidity [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extracts produced with colloidal silicon dioxide had better flow characteristics and a reduced tendency to agglomerate compared to other adjuvants. However, the high load of the plant constituents and reduced particle sizes could cause flow problems, which could lead to unfavorable behavior in conditions of environmental humidity [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the results obtained by Vasconcelos et al [15] and Loch-Neckel et al [16] in studies with the dry extracts of Schinus terebinthiflius raddi and Haematococcus pluvialis, respectively, they showed that the higher concentrations of Aerosil ® influenced the drying process yield. However, the variation of the inlet temperature had no significant influence.…”
Section: Spray-drying Process and Characterization By Semmentioning
confidence: 94%
“…Some chemical and physical properties of drugs are related to the characteristics of the particle size, shape, and morphology. Such characteristics influence the formulation homogeneity, dissolution rate, and bioavailability of bioactive compounds, which are tested for the performance study of the desired intermediate and final products [16]. Table 1 shows the averages of the number of particles calculated by the ImageJ ® software (ImageJ ® 64-bit Java 1.8.0_112 for Windows, Bethesda, MD, USA).…”
Section: Sem Analysismentioning
confidence: 99%